Penerapan Metode TOPSIS dalam Pemilihan Guru Tenaga Harian Lepas (THL) di SD N XYZ - Tangka, George Morris William; Yahuda Putra, Edson (Jurnal Informatika dan Komputer, 2024)
In today's digital era, information systems play a crucial role in operational efficiency and effectiveness, particularly in decision-making processes. This research focuses on the use of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for selecting Temporary Daily Workers (THL) teachers at SDN XYZ. The study utilizes data collected through observations and interviews with five THL teacher candidates, who were evaluated based on criteria including educational background, proximity of residence, interview performance, and personality. The weights of each criterion were determined based on their relevance to the desired position. The results indicate that the TOPSIS method is effective in helping the school identify relevant criteria and evaluate the relative performance of candidates based on the established criteria, thereby facilitating the decision-making process and improving the quality of education at SDN XYZ. Based on the analysis using the TOPSIS method, the THL teacher with the alternative code A had the best relative performance and met the established criteria, making them the recommended choice for the best THL teacher to be hired at SDN XYZ. These findings demonstrate that the application of the TOPSIS method can enhance objectivity and accuracy in the employee selection process.